Hukum Adat Sasi Larvul Ngabal Perspektif Fiqh Al-Bi'ah - Mahdi Temarwut; Soni Zakaria; Moh. Nurhakim (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The purpose of this research to analyze how sasi is practiced in Larvul Ngabal customary law and how sasi Larvul Ngabal customary law from the perspective of Fiqh al-Bi’ah. This study uses qualitative methods with the type of field research. There were 5 informants in this study, consisting of village priests, youth leaders, and 3 members of the community. Data collection techniques used as observation, interviews, and documentation. The data analysis used is data collection, data presentation, and data verivication or drawing conclusion. The result of this study indicate the customary law of sasi Larvul Ngabal basically has the same principles as Fiqh al-Bi’ah in protecting and preserving the invironment. Philosopically, the customary law of sasi Larvul Ngabal originates from noble cultural values which are transformed into basic rules in life. While Fiqh al-Bi’ah is sourced from the authentic Al-Qur’an, contains efforts, ways, ang attitudes towards life towards the environment.